Glucocorticoids Induce Apoptosis in Human Monocytes: Potential Role of IL-1β - Michael Schmidt; Hans‐Gerd Pauels; Norbert Lügering; Andreas Lügering; W Domschke; Torsten Kucharzik (1999)
Abstract Glucocorticoids (GC) are potent anti-inflammatory and immunosuppressive agents that act on a variety of immune cells, including monocytes and macrophages. However, the exact cellular mechanisms underlying this anti-inflammatory capacity are still unknown. In our study, we determined the induction of apoptosis by GC in human monocytes. Peripheral blood monocytes were isolated by density centrifugation methods with a purity of >90% and were cultured in RPMI 1640 medium. Monocyte apoptosis was determined by four independent methods, including annexin-V staining, TUNEL, DNA-laddering, and typical morphology by means of transmission electron microscopy. TNF-α and IL-1β were measured by ELISA. GC receptor was blocked with mifepristone. Caspase 3 was inhibited with caspase-3 inhibitor (DEVD-CHO). Stimulation with different GC at therapeutic concentrations resulted in monocyte apoptosis in a time- and dose-dependent manner. Necrosis was excluded by propidium iodide staining. Proinflammatory cytokines such as IL-1β and TNF-α were down-regulated by GC treatment. Continuous treatment of monocytes with IL-1β, but not with TNF-α, could almost completely prevent GC-induced cell death. The addition of mifepristone or caspase-3 inhibitor could partially abrogate GC-induced apoptosis as well as GC-induced inhibition of IL-1β. This is the first study to demonstrate induction of apoptosis by GC in human monocytes. GC-induced monocyte apoptosis may be partially mediated through effects on IL-1β production. It is conceivable that GC exert their anti-inflammatory capacity in various diseases, at least in part, by the induction of apoptosis in monocytes.